What Women Want: Lead Considerations for Current and Future Applications of Noninvasive Prenatal Testing in Prenatal Care. Issue 3 (14th May 2014) - Farrell, Ruth M.; Agatisa, Patricia K.; Nutter, Benjamin
Abstract Background Noninvasive prenatal testing (NIPT) will change the delivery of prenatal care for all women, including those considered low risk for fetal chromosomal abnormalities. This study investigated pregnant women's attitudes, informational needs, and decision‐making preferences with respect to current and future applications of NIPT. Methods A survey instrument was used to identify aspects of the decision‐making process for NIPT among low‐risk and high‐risk populations. Results Both low‐risk and high‐risk women (n = 334) expressed interest in incorporating NIPT as a screening test into their prenatal care. Information specific to NIPT's detection rate (86%), indications (77%), and performance in comparison with conventional screens and diagnostic tests (63%) were identified as lead factors when considering its use. The future availability of NIPT as a diagnostic test increased women's willingness to undergo testing for fetal aneuploidy, cancer susceptibility, and childhood‐onset and adult‐onset diseases. Despite its noninvasive aspects, participants expressed the need for a formal informed consent process (71%) to take place before testing. Conclusions This study demonstrates that NIPT will introduce new challenges for pregnant women and their health care practitioners who will be charged with supporting informed decision making about its use. It is critical that obstetric professionals are prepared to facilitate a patient‐centered decision‐making process as its clinical application rapidly changes.